Fertilizer intensification and soil fertility impact on maize yield: Response in northern Ghana - Chapoto, Antony; Sabasi, Darlington; Asante-Addo, Collins (Agricultural and Applied Economics Association, 2015)
Fertilizer use and intensity is low in Sub-Saharan Africa. Further, soil fertility has been declining over the years. These together have potentially been contributing to lower crop yields particularly for smallholder farmers. In this study we examine maize yield response to nitrogen in three Districts in Northern Ghana controlling for a number of covariates including soil fertility which have received less attention in the literature. Results show that soil fertility is crucial in increasing yields in Northern Ghana and increasing nitrogen per ha enhances maize yield up to a certain yield plateau beyond which further increases will not increase yields. Chapoto, Antony; Sabasi, Darlington; Asante-Addo, Collins